2001
DOI: 10.1103/physrevb.63.155315
|View full text |Cite
|
Sign up to set email alerts
|

Density of states of a two-dimensional electron gas at semiconductor surfaces

Abstract: The formation of a two-dimensional ͑2D͒ electron channel at semiconductor surfaces has been studied by high-luminosity and high energy-resolution ultraviolet photoelectron spectroscopy. A large variety of bandbending sources ͑alkali metals, silver and antimony adatoms, cleavage defects͒ on different narrow-gap III-V͑110͒ substrates ͑InAs, InSb͒ has been used. The measured photoemission spectral density in the semiconductor conduction band shows a steplike structure, consistent with the description of a jellium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
(23 reference statements)
1
39
0
Order By: Relevance
“…We focus on InAs, as it is probably the best studied material showing native accumulation layers [1][2][3]9,10,[30][31][32], having as well a large technical application potential [33][34][35]. The band bending at InAs surface depends on its orientation and reconstruction as well as on adsorbates [2,9,10,30,32,[36][37][38][39][40].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on InAs, as it is probably the best studied material showing native accumulation layers [1][2][3]9,10,[30][31][32], having as well a large technical application potential [33][34][35]. The band bending at InAs surface depends on its orientation and reconstruction as well as on adsorbates [2,9,10,30,32,[36][37][38][39][40].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The band bending at InAs surface depends on its orientation and reconstruction as well as on adsorbates [2,9,10,30,32,[36][37][38][39][40]. We use sulfur treatment on the (001) surface in order to control the bending [41].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Weber et al 13 recently showed that in most cases this can be accounted for by the presence of In adatoms on the surface, but for freshly cleaved (110) surfaces no such defect should occur, since cleaving only encourages the growth of vacancies, 18 formed by Langmuir evaporation. 19 They examined the surface states, and showed that they cannot be used to explain charge accumulation either.…”
Section: Introductionmentioning
confidence: 99%
“…A minute amount of adsorbate, such as H, 1 N, 2 Sb, 3,4 Ag, 4, 5 K, 4 Cs, 4,6 Fe, 7 and Nb 8 atoms, or a tiny quantity of surface defects 9 induces a carrier-accumulation layer at an n-type InAs(110) surface. Increasing adsorption gives rise to a gradual formation of a carrier-accumulation layer at the surface.…”
Section: Introductionmentioning
confidence: 99%